The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1152/advan.00130.2016
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of TBL with real patients in neurology education in terms of knowledge retention, in-class engagement, and learner reactions

Abstract: In our medical school, we changed from a lecture-based method to a team-based learning (TBL) method to teach "polyneuropathies" in the neurology clerkship starting from the 2014 to 2015 academic year. Real patients were used instead of written scenarios in TBL sessions. This study aimed to compare former lecture-based and the current TBL methods in terms of knowledge retention, in-class learner engagement, and learner reactions. First, we determined in-class engagement and satisfaction of the students for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 29 publications
2
26
0
3
Order By: Relevance
“…The teaching of content through games was able to contribute to the understanding of the contents previously discussed, besides being an interesting, funny and essential tool in the teaching of human physiology [11]. This is consistent with other studies that have demonstrated that group work is an important pedagogical tool and used in conjunction with games can maximize the students' learning Section name: Title (Arial, 10, italic, left, single paragraph) process [3].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The teaching of content through games was able to contribute to the understanding of the contents previously discussed, besides being an interesting, funny and essential tool in the teaching of human physiology [11]. This is consistent with other studies that have demonstrated that group work is an important pedagogical tool and used in conjunction with games can maximize the students' learning Section name: Title (Arial, 10, italic, left, single paragraph) process [3].…”
Section: Discussionsupporting
confidence: 83%
“…However, the change from a teaching-centered model to student-centered model is still a challenge. Teachers rarely have a specific training in active teaching methods, which could promote their engagement in create new strategies to increase de the students' interest and motivation to be more autonomous [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The active teaching has as main characteristic the insertion of student as a protagonist in the construction of knowledge, using different active methodologies to promote the learning [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The teamwork, an strategy that could be included in study groups, is an efficient alternative of active method to increase the students' learning and interest in the contents [8,9], promoting the students' responsibility for the learning [9]. From this perspective, we propose the creation of a study group using teamwork and other active methods as a way to increase the students' interest and facilitate their learning of human physiology.…”
Section: Introductionmentioning
confidence: 99%